Integrated omics analysis of sweat reveals an aberrant amino acid metabolism pathway in Vogt–Koyanagi–Harada disease. (14th April 2020) - Cui, X; Su, G; Zhang, L; Yi, S; Cao, Q; Zhou, C; Kijlstra, A; Yang, P
Summary: Vogt–Koyanagi–Harada (VKH) disease is an autoimmune disease leading to visual impairment. Its pathogenic mechanisms remain poorly understood. Our purpose was to investigate the distinctive protein and metabolic profiles of sweat in patients with VKH disease. In the present study, proteomics and metabolomics analysis was performed on 60 sweat samples (30 VKH patients and 30 normal controls) using liquid chromatography tandem mass spectrometry. Parallel reaction monitoring (PRM) analysis was used to validate the results of our omics analysis. In total, we were able to detect 716 proteins and 175 metabolites. Among them, 116 proteins (99 decreased and 17 increased) were observed to be significantly different in VKH patients when compared to controls. Twenty-one differentially expressed metabolites were identified in VKH patients, of which 18 included choline, L-tryptophan, betaine and L-serine were reduced, while the rest were increased. Our multi-omics strategy reveals an important role for the amino acid metabolic pathway in the pathogenesis of VKH disease. Significant differences in proteins and metabolites were identified in the sweat of VKH patients and, to some extent, an aberrant amino acid metabolism pathway may be a pathogenic factor in the pathogenesis of VKH disease. Graphical Abstract: Sweat, as an emerging biofluid with the potential to discover immune biomarkers, was used to understand the pathogenic mechanisms of Vogt-Koyanagi-Harada (VKH) disease. In our study, we utilized proteomic and metabolomics analysis to investigate the distinctive composition of sweat in VKH patients. Significant differences in proteins and metabolites were identified in the sweat of VKH patients, and an aberrant amino acid metabolism pathway may be a pathogenic factor in the pathogenesis of VKH disease.